Spatiotemporal patterns of rheumatic heart disease burden attributable to high systolic blood pressure, high sodium diet, and lead exposure (1990 to 2019): a longitudinal observational study - Yanli Zhang; Jun Zhang; Yonggang Liu; Yuzhe Zhou; Lu Ye; Kaiming Chen; Jinghua Jiao (Frontiers in Nutrition)
BackgroundRheumatic heart disease (RHD) continues to be a significant global health concern, exhibiting unique regional disparities. Although there is a noted decline in the burden of RHD, the specific causatives for this decrease remain unclear. This study aims to identify and quantify the spatiotemporal patterns related to the RHD-attributable risk burden.MethodsThe data pertaining to deaths and disability-adjusted life years (DALYs) attributable to RHD risk were drawn from the Global Burden of Disease (GBD) study conducted from 1990 to 2019. These data, categorized by age, gender, and geographical location, highlighted risk factors including diets high in sodium, elevated systolic blood pressure (SBP), and lead exposure. To examine the long-term trends in RHD changes due to these specific risk factors, the average annual percentage change (AAPC) method was used.ResultsDuring the past 30 years, the highest decrease in RHD burden was attributed to high SBP. An AAPC of −2.73 [95% confidence interval (CI): −2.82 to −2.65] and − 2.45 (95% CI: −2.55 to −2.36) in deaths and DALYs was attributable to high SBP, while an AAPC of −3.99 (95% CI: −4.14 to −3.85) and − 3.74 (95% CI: −3.89 to −3.6) in deaths and DALYs was attributed to a diet high in sodium. Moreover, the trends in deaths and DALYs due to lead exposure also showed decreases with an AAPC of −2.94 (95% CI: −3 to −2.89) and − 3.46 (95% CI: −3.58 to −3.34) from 1990 to 2019. Oceania showed an upward trend of the RHD DALYs due to high SBP, with an AAPC of 0.23 (95% CI: 0.13 to 0.33). In general, countries in Oceania, East Asia, and South Asia had higher age-standard deaths and DALY rates of RHD due to diets high in sodium.ConclusionOur study has revealed that high SBP remains the prime risk factor contributing to the RHD burden. There are decreasing spatiotemporal patterns in RHD-related deaths and burdens. Gaining this knowledge is fundamental to making informed public health strategies and clinical decisions, especially concerning risk assessment, screening, and prevention initiatives.